Isolation and characterization of novel bacteriophage vB_KpP_HS106 for Klebsiella pneumonia K2 and applications in foods - Chen, Changrong; Tao, Zhenxiang; Li, Tengteng; Chen, Hong; Zhao, Yong; Sun, Xiaohong (Frontiers in Microbiology, 2023)
The detection rate of Klebsiella pneumoniae in food is increasing, it has emerged as a food pathogen. Global health is threatened due to the emergence of multidrug resistant (MDR) and hypervirulent (hv) K. pneumoniae. Phages have a promising application as antibacterial agents and have the ability to lyse MDR strains. Hence, phage vB_KpP_HS106 against MDR-hv K. pneumoniae strains was isolated from sewage collected from Hospital. It can maintain stable activity at the pH range of 4 to 12 and the temperature range of 4 °C to 50 °C. The maximum adsorption rate of phage HS106 was approximately 84.2% at 6 min. The one-step growth curve analysis showed that the latent period of HS106 was 10 min, the burst size was approximately 183 PFU/cell. Furthermore, whole genome analysis indicated that the genome of phage HS106 was a double-stranded linear 76,430-bp long DNA molecule with 44% GC content. A total of 95 open reading frames were annotated in the HS106 genome, which did not contain any virulence genes or antibiotic resistance genes. Phage HS106 reduced MDR K. pneumoniae in milk by approximately 1.6 log10 CFU/mL at 25 °C and in chicken by approximately 2 log10 CFU/cm 3 at 25 °C. Therefore, vB_KpP_HS106 is a promising alternative to antibiotics for biocontrol against multidrug-resistant K. pneumoniae in foods.